MUNICIPAL ASSIGNMENT AS AN EFFECTIVE SERVICE QUALITY CONTROL TOOL - Albertovna Duborkina, Irina; Pavlovna Sokolova, Antonina; Zhamaletdinovich Sirazhdinov, Rifat; Anatolyevna Petrina, Olga; Nikolaevna Mironova, Marina (Revista Inclusiones, 2019)
At present, a state (municipal) assignment is a mandatory document that needs to be formed and executed to establish the quality indicators of the activity of an institution. This approach follows from Article 69.2 of the Budget Code of the Russian Federation, according to which, a state (municipal) assignment should contain indicators of the quality of the provision of state (municipal) services. Quality indicators for the provision of services provided by state (municipal) institutions should be developed based on the most important problems that service recipients face and comply with applicable regulations.